Effect of permethrin (pyrethroid insecticide) on the biochemical response of the freshwater amphipod Echinogammarus tacapensis (Chevreux and Gauthier, 1924). Issue 1 (2nd January 2018) - Touaylia, Samir; Khazri, Abdelhafidh; Mezni, Ali; Bejaoui, Mustapha
Abstract: Pyrethroids, the widely used pesticides, are highly toxic to aquatic organisms. However, little information is available on their toxicity on crustaceans. We utilized imagoes of Echinogammarus tacapensis to elucidate the effects of sublethal concentrations of permethrin. The LC50 (48, 72, and 96 h) was assessed considering several pesticide concentrations (ranging between 0.5 and 100 ng L −1 ) using the Regtox package and were found to be 13.88, 8.974, and 4.259 ng L −1, respectively. The biomarkers' response was analyzed using animals exposed to 0.35, 0.7, and 1.4 ng/L of permethrin for 4 days. The catalase activity was significantly induced after 48 h of exposure to the three permethrin concentrations. Additionally, the glutathione S-transferase activity was increased in a concentration-dependent manner. However, exposed to C1 (0.35 ng L −1 ), the superoxide dismutase (SOD) activity showed no significant change compared to control values. The hydrogen peroxide (H2 O2 ) rate was found to be similar to the SOD variation. Our findings suggest that permethrin poses a potential threat to freshwater amphipods and thus, the test species can be a useful tool for pesticide toxicity biomonitoring due to their small size, easy husbandry, short life cycle, and high fecundity.